Connecting foraging and roosting areas reveals how food stocks explain shorebird numbers. (30th September 2021) - Bakker, Wiene; Ens, Bruno J.; Dokter, Adriaan; van der Kolk, Henk-Jan; Rappoldt, Kees; van de Pol, Martijn; Troost, Karin; van der Veer, Henk W.; Bijleveld, Allert I.; van der Meer, Jaap; Oosterbeek, Kees; Jongejans, Eelke; et al.
Abstract: Shorebird populations, especially those feeding on shellfish, have strongly declined in recent decades and identifying the drivers of these declines is important for conservation. Changing food stocks are thought to be a key driver of these declines and may also explain why trends have not been uniform across Europe's largest estuary. We therefore investigated how winter population trends of Eurasian oystercatchers ( Haematopus ostralegus ) were linked to food availability in the Dutch Wadden Sea. Our analysis incorporated two spatial scales, a smaller scale focused on roost counting areas and food available to birds in these areas and a larger spatial scale of tidal basins. A novelty in our study is that we quantify the connectivity between roosting and foraging areas, identified from GPS tracking data. This allowed us to estimate food available to roosting birds and thus how food availability may explain local population trends. At the smaller spatial scale of roost counting areas, there was no clear relationship between available food and the number of roosting oystercatchers, indicating that other factors may drive population fluctuations at finer spatial scales. At the scale of tidal basins, however, there was a significant relationship between population trends and available food, especially cockle Cerastoderma edule, . Mortality and recruitment alone could not account for the large fluctuations in bird counts, suggesting that the site choice of wintering migratory oystercatchers may primarily drive these large fluctuations. Furthermore, the relationship between oystercatcher abundance and benthic food stocks, suggests winter shorebird counts could act as ecological indicators of ecosystem health, informing about the winter status of food stocks at a spatial scale of tidal basins. Highlights: Understanding the link between predators and prey is important for conservation. We estimated available prey biomass in foraging areas of GPS-tracked shorebirds. We relate available prey biomass to population trends at shorebird roosting areas. A significant positive relationship was found at the scale of tidal basins. Estimating benthic prey biomass in foraging areas may assist population assessments.